THE EFFECTIVENESS OF ARTIFICIAL INTELLIGENCE BY CHATBOT IN ENHANCING THE STUDENTS’ VOCABULARY - Hutauruk, Bertaria Sohnata; Purba, Rudiarman; Sihombing, Santa; Nainggolan, Maruli (English Education Department at FKIP Nommensen University, 2024)
This research aims to find out the effectiveness of artificial intelligence (AI) by chatbot in enhancing the vocabulary students at FKIP Universitas HKBP Nommensen Pematangsiantar. The focus of the research is on the vocabulary skill in teaching English. This research uses the qualitative research methods and used interview and documentation from the students. There are 30 students for the subject of the research out of 70 students in English Vocabulary class of the first semester in English department of Universitas HKBP Nommensen Pematangsiantar. The results of the research are the artificial intelligence application through chat bot enhance the students’ vocabulary in learning English. The students feel enjoy, fun, easy to learn the English words. It can be applied in writing notes diary, essay paragraph in English. The researcher suggests the user of English such as lectures, teachers to use AI chatbot in the classroom instruction because it can be more effective for the students to get the meaning of the words in English. Hopefully the next reseacher can develop the research for more varying language proficiency. The result is that the artificial intelligence affect to the effectiveness in enhancing English vocabulary of the university students. It shows that all participants are enthusiastic, happy, and motivated because this application is still unfamiliar to participants. Participants also know the use of this application, so they can indirectly learn independently whenever and wherever participants